Induction of endothelial barrier dysfunction by serum factors in rats subjected to traumatic brain injury and hemorrhagic shock. Issue 13 (3rd July 2022) - Ke, Yunbo; Proctor, Julie L.; Zhang, Chenou; Medina, Juliana; Miller, Catriona H. T.; Kim, Junghyun; Grissom, Thomas E.; Birukova, Anna A.; Fiskum, Gary M.; Birukov, Konstantin G.
Abstract: Traumatic brain injury (TBI) has been associated with the development of indirect acute respiratory distress syndrome (ARDS). However, the causative relationship between TBI and lung injury remains unclear. To explore potential mechanisms linking TBI with the development of ARDS, we characterized the effects of serum factors released following TBI and hemorrhagic shock (HS) in a rat model on the pulmonary endothelial cell (EC) barrier dysfunction, a key feature of ARDS. We found that serum samples from animals exposed to both controlled cortical impact (CCI) and HS, but not from sham‐operated rats induced significant barrier dysfunction in human pulmonary artery EC monolayers at 2 days post injury. Thrombin inhibitor and thrombin receptor antagonist attenuated the acute phase of the serum‐induced trans‐endothelial resistance (TER) decline caused by CCI‐HS serum, but not in later time points. However, both the early and late phases of CCI‐HS‐induced EC permeability were inhibited by heparin. The barrier disruptive effects of CCI‐HS serum were also prevented by serum preincubation with heparin‐sepharose. Pulmonary EC treated for 3 h with serum from CCI‐HS rats demonstrated a significant decline in expression of EC junctional protein, VE‐Cadherin, and disassembly of peripheral EC adherens junction complexes monitored by immunostaining with VE‐cadherin antibody. These results suggest that exposure to CCI‐HS causes early and late‐phase barrier disruptive effects in vascular endothelium. While thrombin‐PAR1 signaling has been identified as a mechanism of acute EC permeability increase by CCI‐HS serum, the factor(s) defining long‐term EC barrier disruption in CCI‐HS model remains to be determined. Abstract : We have identified serum factors from rats subjected to traumatic brain injury (TBI) and hemorrhagic shock caused endothelial barrier dysfunction. Endothelial barrier dysfunction is a key feature of acute respiratory distress syndrome (ARDS). The observation shed light on revealing molecular mechanism that explains TBI‐induced ARDS.